'If I don't work, I don't get paid': An Australian qualitative exploration of the financial impacts of acute myeloid leukaemia. (12th November 2021) - Parker, Catriona; Berkovic, Danielle; Wei, Andrew; Zomer, Ella; Liew, Danny; Ayton, Darshini
Abstract: A cancer diagnosis can have significant financial impacts for patients, often resulting from unexpected out‐of‐pocket expenses and a reduced capacity to work. These financial implications have been well characterised quantitatively in common cancers. However, less is known about the lived experience of financial stress, particularly outside the United States and in rarer cancers. This study aimed to explore the perceived financial impact of acute myeloid leukaemia (AML)—a rare haematological malignancy where patients may be particularly vulnerable to financial stress due to the lengthy, specialised and centralised care. The findings provide insight into the patients' lived experience of the personal financial impact of the disease. This Australian qualitative study was undertaken with 11 adults in remission from AML and recruited from their treating hospital. Semi‐structured interviews were transcribed, and data were managed using NVivo. Themes were identified through inductive and deductive analysis using open, axial and thematic coding. Four themes were identified: burden of AML‐attributable costs (e.g. out‐of‐pocket parking and medication expenses); accommodating the AML‐impact on paid work (e.g. early retirement and modifying job tasks); the consequence of financial strain from AML (e.g. using savings and accessing Government welfare) and concerns about the future and future familial financial burden (e.g. securing finances and worry about depleting financial resources). A reduction in or stopping work was perceived as the most burdensome to their current and future finances. The findings demonstrate people with AML experience financial difficulty even within a publically funded healthcare system. Opportunities exist for health services to alleviate some financial burden through reducing or abolishing parking fees for oncology patients and ensuring adequate access to social workers to facilitate access to Government welfare. Improving patients' financial difficulties contributes to improved quality of life, which is congruent to cancer survivorship.